Finite Element Analysis of Stress Distribution in Tooth-Implant-Supported Prostheses: Impact of Periodontal Support, Tooth Count, and Implants - Younesi, Farzan; Soleimanpour, Solmaz; Alihemmati, Mohammad; Bakhtiari, Fatemeh; Taghavi, Farnaz; Jahangiri, Maryam; Shayegh, Shojaedin (Galen Medical Journal, 2024)
Background: Biomechanical factors are crucial for the success of tooth/implant-supported prostheses. Despite advancements in implantology, connecting natural teeth to implants remains challenging due to differences in movement, leading to potential complications. This study investigated the impact of periodontal support, number of teeth, and implants on stress distribution in tooth-implant-supported prostheses using three-dimensional (3D) finite element analysis. Material and Methods: This study utilized 3D finite element analysis to evaluate six virtual tooth/implant-supported prostheses with two levels of periodontal support (normal and weak) and three bridge designs (three units, four units with two dental abutments, and four units with two implants). To create the mandibular bone model, the cone beam computed tomography (CBCT) data from a middle-aged patient was used. One ITI implant (4.1 × 10 mm) was used for the fixture model. Models of teeth and bridges were designed according to the principles of metal-ceramic prosthesis design. A static force of 250 N was applied in vertical and oblique directions (at 45 degrees to the longitudinal axis). Maximum Von Mises stress was calculated in megapascals, and stress contour diagrams were generated. Results: Poor periodontal support resulted in a slight increase in stress on the implant and bone. Increasing the number of teeth and implants significantly reduced the stress on the implant and bone. Stress variations were notably greater when applying oblique forces compared to vertical forces. Conclusion: A tooth with a crown-to-root ratio of 1:1 remains suitable as an abutment. Increasing the number of teeth and implants, along with occlusal adjustment, is recommended to reduce stress in the bone and minimize lateral forces applied to the prosthesis, thereby decreasing the risk of marginal bone loss.